2021
DOI: 10.1007/s12325-021-01836-1
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Validation of the Psoriasis Symptoms and Impacts Measure (P-SIM): A Novel Patient-Reported Outcome Instrument for Patients with Plaque Psoriasis, Using Reported Data from the BE RADIANT Phase 3b Trial

Abstract: Introduction: This analysis assessed the psychometric properties of the Psoriasis Symptoms and Impacts Measure (P-SIM), a novel patientreported outcome (PRO) tool designed to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“… 3 , 4 Data from 3 phase III, multicenter, randomized, double-blind, placebo-, and comparator-controlled clinical trials (BE READY, BE SURE, BE VIVID, BE RADIANT) have been published to date, showing bimekizumab superior efficacy over adalimumab, ustekinumab, and secukinumab. 9 , 10 , 11 , 12 There are data regarding the efficacy of bimekizumab for scalp psoriasis also in clinical trials. In particular, BE VIVID, a 52-week, phase 3, randomized, ustekinumab, and placebo-controlled study included, among the efficacy end points, scalp Investigator’s Global Assessment (IGA) 0/1 response at week 16 in patients with scalp psoriasis at baseline (baseline scalp IGA score of ≥2).…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 Data from 3 phase III, multicenter, randomized, double-blind, placebo-, and comparator-controlled clinical trials (BE READY, BE SURE, BE VIVID, BE RADIANT) have been published to date, showing bimekizumab superior efficacy over adalimumab, ustekinumab, and secukinumab. 9 , 10 , 11 , 12 There are data regarding the efficacy of bimekizumab for scalp psoriasis also in clinical trials. In particular, BE VIVID, a 52-week, phase 3, randomized, ustekinumab, and placebo-controlled study included, among the efficacy end points, scalp Investigator’s Global Assessment (IGA) 0/1 response at week 16 in patients with scalp psoriasis at baseline (baseline scalp IGA score of ≥2).…”
Section: Discussionmentioning
confidence: 99%
“…In general, terms such as little or mild are considered to be small enough to represent a minimal difference. To avoid discussion around the word minimal , some authors prefer the terms clinically important or meaningful …”
Section: Discussionmentioning
confidence: 99%
“…7 Data from three Phase III, multicenter, randomized, double-blind, placebo-and comparator-controlled clinical trials showed bimekizumab superior efficacy over adalimumab, ustekinumab, and secukinumab. [8][9][10] In all phase 3 trials, bimekizumab was also well tolerated, with a safety profile similar to the other biologic drugs tested, except for a higher frequency of oral candidiasis. [8][9][10] To date, no real-life experiences or case series regarding bimekizumab for psoriasis are available in literature, due to its very recent approval.…”
mentioning
confidence: 88%
“…[8][9][10] In all phase 3 trials, bimekizumab was also well tolerated, with a safety profile similar to the other biologic drugs tested, except for a higher frequency of oral candidiasis. [8][9][10] To date, no real-life experiences or case series regarding bimekizumab for psoriasis are available in literature, due to its very recent approval. We herein present the first case of EP successfully and rapidly treated with bimekizumab, reaching PASI100 already at Week 4 maintaining response up to Week 12.…”
mentioning
confidence: 88%